Role of 18F-PSMA-1007 PET/CT-derived quantitative volumetric tumor parameters in cytoreductive radical prostatectomy selection for patients with low-volume metastatic hormone-sensitive prostate cancer: a retrospective study - Junjie Fan; Ke Xu; Zhangdong Jiang; Chaosheng Gan; Hao Song; Guoqiang Gao; Guojing Wang; Qiyuan Kang; Liang Luo; Zhuonan Wang; Dalin He; XiaoYi Duan; et al. (BMC Cancer)
Abstract Background Cytoreductive radical prostatectomy (cRP) has emerged as a promising therapeutic approach for low-volume metastatic hormone-sensitive prostate cancer (mHSPC), but the best candidates for cRP are still unknown. This study aims to explore the potential value of 18F-PSMA-1007 PET/CT-derived quantitative volumetric tumor parameters in cRP treatment selection among patients with low-volume mHSPC. Methods A total of 122 patients with primary low-volume mHSPC who underwent 18F-PSMA-1007 PET/CT followed by systemic therapy alone or plus cRP were included. The whole-body PSMA-derived tumor volume (PSMA-TV) was defined as the total volume of whole-body PSMA-avid tumor lesions, and prostate PSMA-TV was defined as the volume of prostate PSMA-avid tumor lesions. Spearman’s correlation was used to analyze the relationships between whole-body PSMA-TV and clinicopathological characteristics. The primary endpoint was progression-free survival (PFS), and Cox regression analyses were performed to explore the independent predictors for PFS. Results Among 122 patients, 37 (30.32%) underwent systemic therapy plus cRP. The median and optimal cutoff values of the whole-body PSMA-TV were 71.68 cm3 (41.28–157.41 cm3) and 78.57 cm3, respectively. Whole-body PSMA-TV was positively correlated with prostate-specific antigen (PSA), and patients with nonregional lymph node (NRLN) metastases had a greater whole-body PSMA-TV (P = 0.001). Cox regression analyses revealed that cRP, lower whole-body PSMA-TV and the absence of NRLN metastases were associated with better PFS (all P < 0.05). Subgroup analyses revealed that patients with a low whole-body PSMA or no NRLN metastases had a significant improvement in PFS for cRP versus no cRP (HR: 8.26; 95% CI: 2.72–25.06, P = 0.001; HR: 2.71; 95% CI: 1.25–5.93, P = 0.018). Moreover, among patients with higher prostate PSMA-TV and prostate PSMA-TV/whole-body PSMA-TV, cRP also significantly prolonged PFS compared with those without cRP (HR: 3.49; 95% CI: 1.49–8.18, P = 0.004; HR: 8.54; 95% CI: 2.47–29.50, P = 0.013). Conclusion In management of primary low-volume mHSPC, whole-body and prostate PSMA-TV evaluations based on 18F-PSMA-1007 PET/CT could be helpful to identify the most suitable candidates for cRP. Trial registration Retrospectively registered.